Time-varying volatility spillovers between oil prices and precious metal prices. (October 2020) - Yıldırım, Durmuş Çağrı; Cevik, Emrah Ismail; Esen, Ömer
Abstract: This paper tackles whether there is a return and volatility spillover effect between oil price and precious metal prices such as gold, silver, platinum, and palladium using the causality-in-variance test approach proposed by Hong (2001). This study utilizes the daily data covering the period from 1990 to 2019 and the empirical findings reveal that there is causality-in-mean relation running from the oil return series to precious metal return series. The causality-in-mean test results show that oil price is Granger cause of all precious metals. Similarly, we find a volatility spillover effect from the oil market to the precious metal market according to the causality-in-variance test results. On the other hand, we find evidence in favor of the bidirectional volatility spillover effect between oil and silver return series. Also, the volatility spillover effect from oil to platinum seems to be weak when it is compared to the other precious metals. Moreover, the time-varying causality-in-variance test results provide a different picture because the null hypothesis of no volatility spillover from precious metals to oil is rejected at specific periods. More interestingly, we find that there is a sequential feedback relationship between oil and silver. Finally, the volatility spillover effect from the oil market to the precious metal markets seems to be strong specifically after the 2000s. Highlights: Return and volatility spillover effects between oil price and precious metal prices are examined. Time-varying causality-in-variance test is employed. Volatility spillover effects from the oil market to the precious metal market are found. Intensity of spillovers during periods of turmoil reduces the benefits of portfolio diversification. Volatility spillovers among commodity markets should be considered by portfolio and risk managers.